Adsorption kinetics, equilibrium and radiation effect studies of radioactive cesium by polymer-based adsorbent - Olatunji, Michael Adekunle; Khandaker, Mayeen Uddin; Mahmud, Habibun Nabi Muhammad Ekramul (John Wiley & Sons, 2017)
Electroactive polypyrrole has been synthesized by oxidative polymerization of pyrrole using ferric chloride hexahydrate as oxidant in the presence of sodium dodecylbenzene sulfonate (SDBS), and used to remove radioactive cesium from aqueous solution. The SDBS-doped polypyrrole (PPy/SDBS) adsorbent was characterized by Field emission scanning electron microscopy, X-ray diffraction and Fourier transform infrared techniques. A rapid and efficient adsorption of 137Cs radionuclide with a maximum sorption capacity of 26.2 mg/g has been achieved at 313 K. The kinetic data show the best fitting by the pseudo first-order model while the Langmuir model properly reproduced the isotherm data. The thermodynamics parameters revealed an endothermic and spontaneous nature of the adsorption process. The adsorption efficiency shows only an insignificant variation with the gamma-ray doses of 100 and 200 kGy. Considering the toxicity and nonbiodegradable nature of radioactive cesium, SDBS-doped polypyrrole could be a good adsorbent for the recovery of 137Cs from radioactive effluents.